The influence of sleep disturbances and sleep disorders on pain outcomes among veterans: A systematic scoping review. (April 2021) - Saconi, Bruno; Polomano, Rosemary C.; Compton, Peggy C.; McPhillips, Miranda V.; Kuna, Samuel T.; Sawyer, Amy M.
Summary: Chronic nonmalignant pain, sleep disturbances and sleep disorders are highly prevalent conditions among U.S. military veterans. Evidence summaries highlight the influence of sleep on pain outcomes in the general adult population but not for the military veteran population. This is a significant gap as U.S. military veterans are an exceedingly high-risk population for both chronic pain and sleep disturbances and/or disorders. We aimed to review the influence of sleep disturbances and sleep disorders on pain outcomes among veterans with chronic nonmalignant pain. A systematic scoping review was conducted using PubMed/Medline, EMBASE, Scopus, CINAHL, and PsycINFO. Twenty-six out of 1450 studies from initial search were included in this review resulting in a combined sample size of N = 923, 434 participants. Sleep disturbances and sleep disorders were associated with worse pain outcomes among veterans with chronic pain. Treatment-induced sleep improvements ameliorated pain outcomes in veterans with sleep disorders and sleep disturbances. Research is indicated to address an overlooked pain treatment opportunity – that of sleep disturbance and sleep disorder management.